Identification and Functional Analysis of Novel Human Growth Hormone Secretagogue Receptor (GHSR) Gene Mutations in Japanese Subjects with Short Stature - Inoue, Hiroshi; Kangawa, Natsumi; Kinouchi, Atsuko; Sakamoto, Yukiko; Kimura, Chizuko; Horikawa, Reiko; Shigematsu, Yosuke; Itakura, Mitsuo; Ogata, Tsutomu; Fujieda, Kenji (The journal of clinical endocrinology and metabolism, 2011)
Context:Short stature (SS) is a multifactorial developmental condition with a significant genetic component. Recent studies have revealed that rare deleterious mutations in the GH-secretagogue receptor type 1A (GHSR1A) gene could be a cause of familial SS or GH deficiency.Objective:The aim of this study was to evaluate the contribution of GHSR1A mutations to the molecular mechanism underlying SS in Japanese subjects.Methods:We performed mutational screening of the GHSR1A gene in 127 unrelated Japanese SS patients diagnosed with either isolated GH deficiency or idiopathic SS. Identified mutations were analyzed in 188 control subjects, and their functional properties were examined in a heterologous expression system.Results:Four novel heterozygous GHSR1A mutations were identified (ΔQ36, P108L, C173R, and D246A). Expression studies demonstrated that these mutations had varying functional consequences: 1) all mutations showed a loss-of-function effect on the constitutive signaling activity of GHSR1A, but the degree of loss varied widely; 2) C173R caused intracellular retention of the mutated protein, resulting in total loss of receptor function; 3) P108L resulted in a large decrease in binding affinity to ghrelin, without affecting its surface expression; 4) D246A uniquely impaired agonist- and inverse agonist-stimulated receptor signaling; and 5) ΔQ36 showed only a subtle reduction in constitutive activity. The cumulative frequency of these putative functional mutations was significantly higher in the patient group than in controls (4.72 vs. 0.53%; P = 0.019; odds ratio = 9.28; 95% confidence interval, 1.10–78.0).Conclusions:Our results suggest that GHSR1A mutations contribute to the genetic etiology of SS in the Japanese population.